2020
DOI: 10.1123/jpah.2019-0272
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity Among Immigrant Children: A Systematic Review

Abstract: Background: The health benefits of physical activity (PA) for children are well documented. However, little is known about PA patterns among immigrant children. Methods: The authors reviewed research on PA patterns of immigrant children. The inclusion criteria included peer-reviewed articles published from January 2010 to May 2018 in English, French, or Spanish that included primary-school-aged (6–12 y) children, and data on immigration status. Results: A total of 11 articles were included in the analyses. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 42 publications
0
16
0
1
Order By: Relevance
“…The most notorious are those more related to the dependent variable construct because of their conceptual proximity to both variables. Thus, the direct relationships between physical exercise (0.239) [ 11 , 12 , 13 , 14 , 16 ] and physical activity (0.205) [ 22 , 23 , 24 , 25 ] with sports stand out, the former being the most relevant of all the variables. This can be explained by the relationship between both manifestations of human motor activity, which results in a positive tendency among those who practise any ordered and systematised physical activity, entailing a step forward in the regulation and institutionalisation of human motor activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most notorious are those more related to the dependent variable construct because of their conceptual proximity to both variables. Thus, the direct relationships between physical exercise (0.239) [ 11 , 12 , 13 , 14 , 16 ] and physical activity (0.205) [ 22 , 23 , 24 , 25 ] with sports stand out, the former being the most relevant of all the variables. This can be explained by the relationship between both manifestations of human motor activity, which results in a positive tendency among those who practise any ordered and systematised physical activity, entailing a step forward in the regulation and institutionalisation of human motor activity.…”
Section: Discussionmentioning
confidence: 99%
“…However, this work focuses only on studies on young immigrants, analysing the underlying dimensions of a healthy lifestyle—exercise, physical activity and nutrition, among others—and their effects on practising sports. This differentiation with respect to local students is made because the literature has already found that immigrants adopt unhealthier habits when they move to the destination country [ 15 ] and that these effects also impact their children, who end up having worse health and habits than their local counterparts [ 11 , 12 , 13 , 14 , 16 , 17 , 18 ]. In this sense, it is important to mention that although the majority of studies found differences between locals and immigrants at different stages, some have found few or no differences in physical [ 11 ], physiological or behavioural [ 19 , 20 ] activity.…”
Section: Introductionmentioning
confidence: 99%
“…First and foremost, it is important to prioritize support for the most vulnerable groups when promoting PA. A recent systematic review concluded that the immigration process is known to have a negative impact on youth PA. Thus, youth with a migrant background represent a group at risk of low PA (Lacoste et al, 2020). Language, socioeconomic status, and discrimination (Taverno et al, 2010) are factors that particularly hinder organized physical activity among youth with a migrant background, which might underlie the finding that the more recent the immigration, the less PA practiced by immigrant youth (Kukaswadia et al, 2014).…”
Section: Intervention Targets To Increase Physical Activity Among Youthmentioning
confidence: 99%
“…The two largest in terms of sample size (N = 361) are from the Danish TEACHOUT research project on Udeskole practices (Schneller, Duncan, et al, 2017;. None of these studies focused on students with a migrant background, a group that is less active and spends less time outdoors (Conrad et al, 2013;Lacoste et al, 2020). Furthermore, they all come from Scandinavia or Finland, regions known to be at the forefront of outdoor learning practices.…”
Section: Studies Of Physical Activity In Outdoor Learning Settingsmentioning
confidence: 99%
“…Agreeing with this, ref. [110] indicates that immigrant students present lower academic measures when suffering from the impact of adaptation to a new context. Their integration in the host country significantly affects the development of these skills [111].…”
Section: Social Skills and Academic Success In Immigrant Studentsmentioning
confidence: 99%